PENILAIAN PENGUNJUNG DISABILITAS PADA FASILITAS OBJEK WISATA TAMAN BUDAYA GARUDA WISNU KENCANA BALI - Novia Dolorosa Br Simarmata; Andi Moh Rifiyan Arief (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This study was conducted to determine the assessment of disability visitors at the amenities of the Garuda Wisnu Kencana Cultural Park in Bali. This research aimed: (1) to determine the assessment of disability visitors at the Garuda Wisnu Kencana Cultural Park tourist attraction facilities, (2) to determine the manager's efforts to manage facilities for disability visitors at the Garuda Wisnu Kencana Cultural Park. This study uses the Pitojo theory which discusses the distribution of tourist facilities in order to explain the phenomena found in the field.This research uses a quantitative approach to clarify the issues raised in this research. While the data collection technique uses the method of observation, interviews, questionnaires and documentation. The sample in this research was 100 respondents. The results of this study indicate that based on research results obtained from the assessment of disability visitors at the amenities of the Garuda Wisnu Kencana Cultural Park in Bali, it is considered very good and disability visitors feel very satisfied with the facilities available. This is evidenced by the acquisition of a total facility total score of 21.965 points. Keyword: Satisfaction, Disability visitors, Amenities